Development Of Halal Food Textbooks To Support Culinary Students' Achievement Of SDGs - Ratna Palupi Nurfatimah; Nugrahani Astuti; Hidayatun Muyasyaroh; Fitri Komala Sari; Hanif Naufal Ahmi (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
The background of this research is the increasing demand for the Indonesian halal industry and the achievement of SDGs, as well as the limited comprehensive Halal Food teaching materials in universities. The aim of the research to develop and determine the feasibility of a textbook for undergraduate students of Culinary Arts Education, UNESA. The novelty of this research lies in the integration of three pillars: sharia aspects, certification regulations, and practical food technology (critical points) relevant to culinary vocations. The method used is the Research and Development (R&D) 4D model (Define, Design, Develop, Disseminate), the textbook was validated by 3 experts (material and media) and tested limited to 65 students as users. The results of quantitative descriptive analysis and data triangulation showed that the textbook was declared "Very Feasible". User responses were very positive, where 86.2% of students rated the book "Feasible for Use". The highest quantitative scores were in the SDGs Insight category (3.71/4.00) and Material Construction Feasibility (3.65/4.00), which validated the success of the substance. The main areas of improvement identified consistently by experts and students were the technical aspects of visual presentation, such as cover design, layout, and image resolution (3.50/4.00). It was concluded that this textbook is very valid and worthy of being implemented as the main teaching material after improvements to the visual design. Implementation of the textbook in learning activities is an assignment for students regarding the analysis of critical halal points in MSME products around the campus.